ANALISIS STRATEGI PEMASARAN TERHADAP PELAYANAN KESEHATAN PADA ERA JAMINAN KESEHATAN NASIONAL DI RUMAH SAKIT PARU SURABAYA - Juliani Pudjowati; Sri Wahyuni Rochmawati; Nova Retnowati; Farida Yuni Rahmawati; Mamak Balafif; Achmad Syamsudin (Universitas Prof. Dr. Hazairin SH, 2021)
The purpose of this study wasto determine the marketing strategy, the effectiveness of the marketing strategy, the obstacles in carrying out the marketing strategy, and how to overcome the obstacles in carrying out the marketing strategy of health services during the JKN (National Health Insurance) era at the hospital. Lung Surabaya. This study uses a qualitative approach and the researcher as the key instrument. This technique of determining key informants is carried out before or when conducting field research. The technique used before the field research is the judgment of the researcher. Meanwhile, the technique of determining key informants during field research is snowball or snowball technique. The judgment technique is carried out using certain criteria that have been previously determined by the researcher in this study, namely the director, then using the snowballing method totaling 5 key informants. The validity of the data using the triangulation method. Analysis of the data from this study using data reduction, data collection, data display, conclusions